INVESTMENT IN SOLAR COLLECTORS ON THE EXAMPLE OF A CITY AND COMMUNE BŁAŻOWA - Danuta Proszak-Miąsik; Justyna Darmochwał; Jakub Gargała (Journal of Civil Engineering, Environment and Architecture, 2021)
Due to depleting natural resources and increasing costs of their extraction, alternative energy sources are becoming an import ant branch of energy. Their impact on environmental pollution is much lower than with conventional energy sources, or if you consider solar energy zero. Currently, many programs are subsidizing the costs of assembly and devices using renewable power sources, the beneficiaries of which are residents of municipalities participating in projects that are largely financed by the European Union. Solar collectors are devices used to heat water for everyday use in homes and farms. Thanks to adequate sunlight they are able to provide comfortable medium temperature conditions for most of the year. This significantly reduces bills for natural gas or electricity – depending on the type of water heater. Collectors are divided into 3 types: flat, vacuum and focusing. Their heat conducting medium may be liquid or gas. Photovoltaic devices, solar collectors and biomass stoves were used in the commune and the city of Błażowa. Focusing on collectors, it can be seen that the flat collectors have been selected, which have a good price-performance ratio and the energy obtained. 210 households benefited from the co-financing program. Most people decided to install collectors on residential buildings because their own contribution depended on the location of the devices – 8% VAT for mixing buildings and 23% VAT for farm buildings. The cost of the set on a residential building depended on the power and ranged from 2,488.00 [zł] to 3,131.60 [zł], which with a net price without co-financing of respectively 8600,00 [zł] to 10,770.00 [zł] gives a very large saving. The effect of the investment is about 75% energy saving, which in a few years allows you to recover the money invested in collectors.